Diagnosis and comparative analysis of surgical treatment of patients with liver alveococcosis - V. S. Panteleev; M. A. Nartaylakov; I. Z. Salimgareev; A. S. Petrov (Acta Biomedica Scientifica, 2023)
Rationale. Alveococcosis is a rare disease, its diagnosis and treatment depend on surgical techniques, equipment and clinical experience. The aim. To develop a diagnostic algorithm and compare the results of surgical treatment of patients with liver alveococcosis in different periods of time.Materials and methods. At the first stage, we carried out a retrospective analysis (1995–2007) of 33 patients with alveococcosis (a comparison group). At the second stage, a prospective clinical study (2008–2021) was performed on 39 patients (the main group). The number of patients was determined in accordance with the inclusion and exclusion criteria, and the study groups were comparable in age, sex, parasite localization (p > 0.05). For the names of operations, the WHO classification of alveococcosis was used.Results. In the main group, there is an increase in the applicability of: enzyme immunoassay; ultrasound and computed tomography; biopsy. Complications decreased by 2.7 times from 54.6 % in the comparison group to 20.6 % in the main group (χ2 = 8.97; df = 1; p = 0.003). The average duration of operations, as well as the average volume of blood loss in the comparison group and the main group were, respectively: with atypical resection – 220.4 and 180.2 min (p = 0.003), 640.1 and 480.0 ml (p = 0.005); with anatomical resection – 296.2 and 247.2 min (p = 0.002), 1450.2 and 1150.3 ml (p = 0.018); with cytoreductive resection – 230.2 and 200.1 min (p = 0.004), 860.3 and 670.4 ml (p = 0.001). There were 13 (39 %) cytoreductive resections in the comparison group, and 3 (8 %) in the main group (χ2 = 4.74; df = 1; p = 0.029).Conclusion. Timely diagnosis of alveococcosis leads to an increase in the number of radical resections, and modern surgical technologies and equipment can reduce the time of surgery, blood loss and the number of complications.